Phosphorus monolayer doping (MLD) of silicon on insulator (SOI) substrates - Kennedy, Noel; Duffy, Ray; Eaton, Luke; O’Connell, Dan; Monaghan, Scott; Garvey, Shane; Connolly, James; Hatem, Chris; Holmes, Justin D.; Long, Brenda (Beilstein Journal of Nanotechnology, 2018)
This paper details the application of phosphorus monolayer doping of silicon on insulator substrates. There have been no previous publications dedicated to the topic of MLD on SOI, which allows for the impact of reduced substrate dimensions to be probed. The doping was done through functionalization of the substrates with chemically bound allyldiphenylphosphine dopant molecules. Following functionalization, the samples were capped and annealed to enable the diffusion of dopant atoms into the substrate and their activation. Electrical and material characterisation was carried out to determine the impact of MLD on surface quality and activation results produced by the process. MLD has proven to be highly applicable to SOI substrates producing doping levels in excess of 1 × 1019 cm−3 with minimal impact on surface quality. Hall effect data proved that reducing SOI dimensions from 66 to 13 nm lead to an increase in carrier concentration values due to the reduced volume available to the dopant for diffusion. Dopant trapping was found at both Si–SiO2 interfaces and will be problematic when attempting to reach doping levels achieved by rival techniques.
Keywords: CMOS; doping; monolayer; silicon; silicon on insulator (SOI)

Proceedings of the 14th International Conference - Renau, A.; Scheuer, J. T. (Comparison of plasma doping and beamline technologies for low energy ion implantation, Ion Implantation Technology 2002, Taos, New Mexico, USA, 22.9.2002-27.9.2002)

(untitled) - Duffy, R.; Van Dal, M. J. H.; Pawlak, B. J.; Kaiser, M.; Weemaes, R. G. R.; Degroote, B.; Kunnen, E.; Altamirano, E. (Appl. Phys. Lett., 2007)

(untitled) - Wood, B. S.; Khaja, F. A.; Colombeau, B. P.; Sun, S.; Waite, A.; Jin, M.; Chen, H.; Chan, O.; Thanigaivelan, T.; Pradhan, N.; Gossmann, H.-J. L.; Sharma, S.; et al. (ECS Trans., 2013)

(untitled) - Khaja, F. A.; Gossmann, H.-J. L.; Colombeau, B.; Thanigaivelan, T. (Bulk FinFET junction isolation by heavy species and thermal implants, 2014 20th International Conference on Ion Implantation Technology (IIT), Portland, OR, USA, 26.6.2014-4.7.2014)

(untitled) - Ho, J. C.; Yerushalmi, R.; Jacobson, Z. A.; Fan, Z.; Alley, R. L.; Javey, A. (Nat. Mater., 2008)

(untitled) - Ye, L.; González-Campo, A.; Núñez, R.; de Jong, M. P.; Kudernac, T.; van der Wiel, W. G.; Huskens, J. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Puglisi, R. A.; Caccamo, S.; D’Urso, L.; Fisichella, G.; Giannazzo, F.; Italia, M.; La Magna, A. (Phys. Status Solidi A, 2015)

(untitled) - O’Connell, J.; Collins, G.; McGlacken, G. P.; Duffy, R.; Holmes, J. D. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Alphazan, T.; Álvarez, A. D.; Martin, F.; Grampeix, H.; Enyedi, V.; Martinez, E.; Rochat, N.; Veillerot, M.; Dewitte, M.; Nys, J.-P.; Berthe, M.; Stiévenard, D.; et al. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Taheri, P.; Fahad, H. M.; Tosun, M.; Hettick, M.; Kiriya, D.; Chen, K.; Javey, A. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Long, B.; Alessio Verni, G.; O’Connell, J.; Shayesteh, M.; Gangnaik, A.; Georgiev, Y. M.; Carolan, P.; O’Connell, D.; Kuhn, K. J.; Clendenning, S. B.; Nagle, R.; Duffy, R.; et al. (Mater. Sci. Semicond. Process., 2017)

(untitled) - O’Connell, J.; Napolitani, E.; Impellizzeri, G.; Glynn, C.; McGlacken, G. P.; O’Dwyer, C.; Duffy, R.; Holmes, J. D. (ACS Omega, 2017)

(untitled) - Ye, L.; González-Campo, A.; Kudernac, T.; Núñez, R.; De Jong, M.; van der Wiel, W. G.; Huskens, J. (Langmuir, 2017)

(untitled) - Kumar, S.; Murshid, A. M.; Loan, S. A. (A novel hybrid doping based SOI MOSFET, 2016 3rd International Conference on Devices, Circuits and Systems (ICDCS), Coimbatore, India, 3.3.2016-5.3.2016)

(untitled) - Jacoboni, C.; Canali, C.; Ottaviani, G.; Quarante, A. A. (Solid-State Electron., 1977)

(untitled) - Perego, M.; Seguini, G.; Arduca, E.; Frascaroli, J.; De Salvador, D.; Mastromatteo, M.; Carnera, A.; Nicotra, G.; Scuderi, M.; Spinella, C.; Impellizzeri, G.; Lenardi, C.; et al. (Nanoscale, 2015)

(untitled) - Arduca, E.; Mastromatteo, M.; de Salvador, D.; Seguini, G.; Lenardi, C.; Napolitani, E.; Perego, M. (Nanotechnology, 2016)

(untitled) - Oh, J.; Im, K.; Ahn, C.-G.; Yang, J.-H.; Cho, W.-j.; Lee, S.; Park, K. (Mater. Sci. Eng., B, 2004)

(untitled) - Acosta Alba, P.; Kerdiles, S.; Mathieu, B.; Kachtouli, R.; Mazzamuto, F.; Toque-Tresonne, I.; Huet, K.; Besson, P.; Veillerot, M.; Aussenac, F.; Fenouillet-Beranger, C. (Nanosecond Laser Annealing for Phosphorous Activation in Ultra-Thin Implanted Silicon-On-Insulator Substrates, 2016 21st International Conference on Ion Implantation Technology (IIT), Tainan, Taiwan, 26.9.2016-30.9.2016)

(untitled) - Mastromatteo, M.; Arduca, E.; Napolitani, E.; Nicotra, G.; De Salvador, D.; Bacci, L.; Frascaroli, J.; Seguini, G.; Scuderi, M.; Impellizzeri, G.; Spinella, C.; Perego, M.; et al. (Surf. Interface Anal., 2014)

(untitled) - Lindermuth, J.; Mizuta, S.-I. (Proc. SPIE, 2011)

(untitled) - Van der Pauw, L. J. (Philips Res. Rep., 1958)